Authentic leadership role on organizational innovativeness with creativity and organizational trust - Nella Ladita, Dwi Ratmawati, (Opción, 2020)
One of strategy that can be done by mass media to survive in competitive business situations is make an innovation. Authentic leadership, creativity, and organizational trust are variables that can influence organizational innovativeness, where creativity and organizational trust act as mediation. To analyze the effect of authentic leadership on organizational innovativeness with creativity and organizational trust as mediating variables. Results showed that authentic leadership has a positive and significant influence on organizational innovativeness. Creativity can partially mediates the effect of authentic leadership on organizational innovativeness, while the organizational trust does not mediate the effect of authentic leadership on organizational innovativeness.